2018
DOI: 10.1007/s10340-018-0974-0
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of the risk of Bt-cowpea to non-target organisms in West Africa

Abstract: Cowpea (Vigna unguiculata Walp.) is the most economically important legume crop in arid regions of sub-Saharan Africa. Cowpea is grown primarily by subsistence farmers who consume the leaves, pods and grain on farm or sell grain in local markets. Processed cowpea foods such as akara (a deep-fat fried fritter) are popular in the rapidly expanding urban areas. Demand far exceeds production due, in part, to a variety of insect pests including, in particular, the lepidopteran legume pod borer (LPB) Maruca vitrata.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 85 publications
0
10
0
Order By: Relevance
“…In Egypt, cowpea is promising double purpose forage and seed crop for its green canopy or using it in animal diets as dry seeds, as well as it is a primary source of plant protein for humans and animals in the summer season (HamdAlla et al, 2014). It is the most economically important legume crop in arid regions of sub-Saharan Africa (Ba et al, 2018). However, Singh and Allen (1979) reported that major insect pests of cowpea that cause economic losses are cowpea aphids (Aphis craccivora Koch), leafhoppers (Empoasca spp.…”
Section: Introductionmentioning
confidence: 99%
“…In Egypt, cowpea is promising double purpose forage and seed crop for its green canopy or using it in animal diets as dry seeds, as well as it is a primary source of plant protein for humans and animals in the summer season (HamdAlla et al, 2014). It is the most economically important legume crop in arid regions of sub-Saharan Africa (Ba et al, 2018). However, Singh and Allen (1979) reported that major insect pests of cowpea that cause economic losses are cowpea aphids (Aphis craccivora Koch), leafhoppers (Empoasca spp.…”
Section: Introductionmentioning
confidence: 99%
“…Most cowpea genotypes are highly susceptible to Maruca vitrata, a pod borer which devastates crop yields and naturally resistant germplasm has not been identified. Maruca-resistant cowpea varieties containing the Bacillus thuringiensis (BT) gene have now been developed for Nigerian agricultural production, providing a transgenic platform for cowpea crop improvement [1].…”
Section: Introductionmentioning
confidence: 99%
“…Plant-incorporated protectants (PIPs) are biopesticides such as the gene encoding the Bt toxin that can be introduced into the plant genome that allows the plant to produce this toxin and increases the resistance of the plant to some pests [ 178 ]. For instance, the Cry proteins expressed in Bt cowpeas have shown a less negative effect on nontarget organisms [ 179 ]. Generally, the PIPs available globally for the specific management of M. vitrata and A. fabae are limited, and equally, their impacts on their natural enemies have not been studied; thus, more work has to be done to address this gap.…”
Section: Other Sustainable Alternatives Compatible With Natural Enemies For Managing Maruca Vitrata and Aphimentioning
confidence: 99%